Global Trends in Incidence Rates of Primary Adult Liver Cancers: A Systematic Review and Meta-Analysis - Dasgupta, Paramita; Henshaw, Chloe; Youlden, Danny R.; Clark, Paul J.; Aitken, Joanne F.; Baade, Peter D. (Frontiers in Oncology, 2020)
Background: Primary liver cancer is a leading cause of cancer deaths worldwide. Global burden varies, reflecting geographical distribution of viral hepatitis. Our objective was to perform a systematic review and meta-analysis of published current trends in incidence of adult liver cancers and histological types worldwide. Methods: This study used systematic searches of PubMed, Embase, CINAHL, and Web of Science databases for English-language peer-reviewed articles published from 1 January 2008 to 01 September 2019. Inclusion criteria were population-based studies of adult liver cancer patients with quantitative estimates of temporal trends in incidence for liver cancers and/or histological types. For multiple studies from the same geographical area, only the publication that reported the most recent trends for the same cancer type and population subgroup was included. Review was conducted per PRISMA guidelines. Two authors independently extracted data and critically assessed studies. Proposed contributors to observed trends were extracted from included articles. Study-specific estimates of the annual percentage change (APC) in incidence rates with 95% confidence intervals (CIs) were pooled using random-effects meta-analysis models. Heterogeneity was measured using the I2 statistics and publication bias evaluated using funnel plots and Egger's tests. Results: Overall, 53 studies met the inclusion criteria, of which 31 were included in the meta-analysis. Overall, pooled APC estimates were +0.8 (95% CI −0.3, +2.0) for liver cancers combined, +2.6 (95% CI +1.2, +4.0) for hepatocellular carcinoma (HCC), and +4.3 (95% CI +2.5, +6.1) for intrahepatic cholangiocarcinoma. Subgroup analyses indicated increasing trends for liver cancers (APC +3.2, 95% CI +2.5, +3.9) and HCC (APC +3.6, 95% CI +2.9, +4.4) in the region of North America/Europe/Australia, whereas corresponding trends were decreasing (APC −1.7, 95% CI −2.2, −1.1) and stable (APC −0.7, 95% CI −1.9, +0.5) in Asia, respectively. Conclusions: Incidence is increasing for adult liver cancers and HCC in Western countries, whereas trends are decreasing in the Asian region, although still remaining high. Our findings highlight the importance of viral hepatitis control and lifestyle interventions to reduce global liver cancer burden. Ongoing surveillance is also vital to detect early shifts in incidence trends.